2021
DOI: 10.3390/laws10020032
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Legal Analysis of Cryptocurrency: Scientific Views from Russia and the Muslim World

Abstract: The article is devoted to the analysis of cryptocurrency as a new phenomenon in the modern global economic processes and legal institutions. The relevance of the study is predetermined by the very specifics of such a phenomenon as cryptocurrency consisting of a distributed ledger technology, which determines the peculiarities of issuing, storing and performing operations with cryptocurrency. Moreover, the cryptocurrency turnover directly correlates with the national legislation of individual countries, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…• People are more likely to engage in cryptocurrency use if they consider it useful (H6) in terms of enabling easy, fast, and low-cost transactions or a high yield on investment (Arias-Oliva et al, 2019;Baur et al, 2018;Jankeeparsad and Tewari, 2018;Mendoza-Tello et al, 2018;Nuryyev et al, 2018), providing a person with joy and comfort in its use (H8) (Abramova and Böhme, 2016;Alharbi & Sohaib, 2021;Nadeem et al, 2020), and enhancing their personal innovativeness (H10) (Sohaib et al, 2019;Sun et al, 2020), but at the same time not bearing a high risk of privacy data leaking (H4a) or financial losses (H4c) (Nofer et al, 2017). • Potential users do not consider security risk as relevant for their attitude toward cryptocurrency (H3b) or their intention to use cryptocurrency (H4b), as they do not perceive cryptocurrency use as risky in terms of technology failure, which is partially consistent with prior literature that argues that the use of cryptocurrencies is usually considered safe due to their cryptographic security (Hileman & Rauchs, 2017;Nadeem et al, 2021;Nuryyev et al, 2018), but also that the impact of security risk depends on a person's knowledge and information about cryptocurrencies (Noreen et al, 2021;Shovkhalov & Idrisov, 2021).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…• People are more likely to engage in cryptocurrency use if they consider it useful (H6) in terms of enabling easy, fast, and low-cost transactions or a high yield on investment (Arias-Oliva et al, 2019;Baur et al, 2018;Jankeeparsad and Tewari, 2018;Mendoza-Tello et al, 2018;Nuryyev et al, 2018), providing a person with joy and comfort in its use (H8) (Abramova and Böhme, 2016;Alharbi & Sohaib, 2021;Nadeem et al, 2020), and enhancing their personal innovativeness (H10) (Sohaib et al, 2019;Sun et al, 2020), but at the same time not bearing a high risk of privacy data leaking (H4a) or financial losses (H4c) (Nofer et al, 2017). • Potential users do not consider security risk as relevant for their attitude toward cryptocurrency (H3b) or their intention to use cryptocurrency (H4b), as they do not perceive cryptocurrency use as risky in terms of technology failure, which is partially consistent with prior literature that argues that the use of cryptocurrencies is usually considered safe due to their cryptographic security (Hileman & Rauchs, 2017;Nadeem et al, 2021;Nuryyev et al, 2018), but also that the impact of security risk depends on a person's knowledge and information about cryptocurrencies (Noreen et al, 2021;Shovkhalov & Idrisov, 2021).…”
Section: Resultssupporting
confidence: 74%
“…Yet, cryptocurrencies have also raised concerns regarding their security and impact on society (Al-Amri et al, 2019). As there is no central authority that monitors this system, users cannot recover their funds in case of theft of cryptocurrencies by malware attacks or their accidental loss (Shovkhalov & Idrisov, 2021). There were also several scams, e.g.…”
Section: Introduction To Cryptocurrencymentioning
confidence: 99%
“…Studies have shown that the rise in unrestricted flow in capital market comes with increased financial and aggregate economic volatility [98]. Notwithstanding, some other studies have shown that given the right policy environment, it is possible to permit cryptocurrency usage and adoption without undue negative impact on the economies of the permitting countries [99][100][101] and in some cases, digital token transactions have developed into significant capital market hubs (Dewey 2019). This view is further underscored by the fact that although several monetary authorities have issued cautions about its use, they are yet to outrightly ban its usage.…”
Section: Cryptocurrencies and Capital Controls/regulationsmentioning
confidence: 99%
“…As for the Russian Federation, the beginning of 2021 was a starting point in the process of regulating the cryptocurrencies domain, by adopting a law to address various issues regarding the issuance, accounting and use of virtual financial assets. In this sense, Russian specialists (Shovkhalov & Idrisov, 2021) appreciate that the level of consolidation of the Russian regulatory framework on cryptocurrencies is not enough, possible developments in the legislative spectrum may arise simultaneously with the development of the virtual currency domain.…”
Section: Analysis Of How the Population Relates To Virtual Currenciesmentioning
confidence: 99%